Does perceived organisational support influence career intentions? The qualitative stories shared by UK early career doctors - Scanlan, Gillian Marion (BMJ Open, 2018)
INTRODUCTION: The wish to quit or take time out of medical training appears to be related, at least in part, to a strong desire for supportive working and learning environments. However, we do not have a good understanding of what a supportive culture means to early career doctors, and how perceptions of support may influence career decision making. Our aim was to explore this in UK Foundation doctors. METHODS: This was a qualitative study using semistructured interviews incorporating a narrative inquiry approach for data collection. Interview questions were informed by the literature as well as data from two focus groups. Interviews were carried out in two UK locations. Initial data coding and analysis were inductive, using thematic analysis. We then used the lens of Perceived Organizational Support (POS) to group themes and aid conceptual generalisability. RESULTS: Twenty-one interviews were carried out. Eleven interviewees had applied for specialty training, while ten had not. Support from senior staff and colleagues influenced participants’ job satisfaction and engagement. Positive relationships with senior staff and colleagues seemed to act as a buffer, helping participants cope with challenging situations. Feeling valued (acknowledgement of efforts, and respect) was important. Conversely, perceiving a poor level of support from the organisation and its representatives (supervisors and colleagues) had a detrimental impact on participants’ intentions to stay working within the National Health Service (NHS). CONCLUSION: Overall, this is the first study to explore directly how experiences in early postgraduate training have a critical impact on the career intentions of trainee/resident doctors. We found perceived support in the early stages of postgraduate training was critical to whether doctors applied for higher training and/or intended to stay working in the NHS. These findings have transferable messages to other contexts struggling to recruit and retain junior doctors.